Improving Students’ Vocabulary Mastery Through Think-Pair- Share with Picture Word Inductive Model (PWIM) - Simon, Maria Kristina (JALL (Journal of Applied Linguistics and Literacy), 2025)
This study aims to improve the English vocabulary mastery of seventh-grade students at SMPK Sang Timur Malang through the implementation of the Think-Pair-Share (TPS) and Picture Word Inductive Model (PWIM) teaching methods. The research was conducted as a classroom action research (CAR) carried out in one cycle consisting of four meetings. Each stage of  the  research included planning, action, observation, and  reflection. Data were collected through observations, tests, reflective journals, questionnaires, and interviews. The findings showed  that  the  combination of  TPS  and  PWIM  effectively improved students’ vocabulary mastery. This was evident from the improvement in test scores, improved student engagement during the learning process, and positive responses toward the methods used. Therefore, this teaching strategy proves to be effective and applicable for supporting vocabulary learning in junior high school English classes.